2015
DOI: 10.7759/cureus.372
|View full text |Cite
|
Sign up to set email alerts
|

Improving Brain Tumor Research in Resource-Limited Countries: A Review of the Literature Focusing on West Africa

Abstract: Neoplasms of the brain are often overlooked in resource-limited countries. Our literature search via AJOL and PubMed demonstrated that brain tumor research is still a rarity in these regions. We highlight the current status, importance, challenges, and methods of improving brain tumor research in West Africa. We suggest that more attention be given to basic, clinical, and epidemiological brain tumor research by national governments, private organizations, international organizations, non-governmental organizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…There are known risk factors associated with brain tumors and these include radiation exposure, hereditary factors, age, sex, ethnicity, infections, and heavy metal exposure 20. Not many studies have been carried out in our environment to elucidate possible risk factors for development of intracranial tumours.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are known risk factors associated with brain tumors and these include radiation exposure, hereditary factors, age, sex, ethnicity, infections, and heavy metal exposure 20. Not many studies have been carried out in our environment to elucidate possible risk factors for development of intracranial tumours.…”
Section: Discussionmentioning
confidence: 99%
“…However, high levels of lead have been associated with development of meningiomas. It has been suggested that ingestion of snails, canned meat and fish may be risk factors for development of meningiomas 20…”
Section: Discussionmentioning
confidence: 99%
“…However, these cases may not reflect the true burden of BTs in Kenya considering KNH remains the main neurosurgical and neurooncological care center. Patient factors, such as healthcare seeking behaviors, health system challenges, including service delivery, health workforce, health system financing, and neurosurgical and neurooncological care are largely overlooked in resource-limited settings, including Kenya [ 25 ]. This may impair health care and service delivery for brain tumors.…”
Section: Discussionmentioning
confidence: 99%
“…The inadequate health resources of many African countries have led to the underestimation of brain cancer incidence (Ngulde et al., 2015 ). This results in underreporting of the negative impacts that brain cancer has on society (Ngulde et al., 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…The inadequate health resources of many African countries have led to the underestimation of brain cancer incidence (Ngulde et al., 2015 ). This results in underreporting of the negative impacts that brain cancer has on society (Ngulde et al., 2015 ). The lack of a healthcare system able to provide adequate diagnostic services and treatment poses a severe challenge to resource‐limited countries.…”
Section: Introductionmentioning
confidence: 99%